THE IMPACT OF COVID-19 ON OPERATIONAL COSTS AT COMMUNICATION AND INFORMATICS SERVICES IN PAREPARE CITY - Abdul Azis; Hasdiana Hasdiana; Nurfitria Nurfitria (Journal AK-99, 2022)
The purpose of this study was to analyze the impact of the operational costs at Communication and Informatics Services in Parepare City before and during the Covid-19 pandemic. This type of research was a comparative qualitative descriptive study by conducting analysis to look for existing phenomena. The results of this study indicate that the amount of expenses increases. Judging from the amount of expenses that are large compared to the allocated budget, the Communication and Informatics Serviceswas experiencing a deficit. One reason is that part of the budget has been diverted to the handling of the Covid-19 disaster. This was done to align with regional financial capabilities in anticipating and strengthening programs deemed capable of tackling Covid-19. To overcome the deficit, it can be done by reducing subsidy expenditures, saving every routine expenditure, evaluating expenditures based on priorities and reducing costs for ineffective programs.